Educational Aspects of Supported Employment as an Exemplification of Actions for the Policy of Social Cohesion Based on Polish Experiences - Jan Sikora (Institute of Social Affairs of the Pedagogical University of Cracow, 2021)
The subject of the article are the considerations regarding the involvement of the education system in the implementation of the social cohesion policy on the example of Polish experiences. An example of a such involvement is the activity in the process of implementing the Supported Employment project, an important element of which is the preparation of job trainers to perform professional tasks. Against the background of the conducted research, the methods of determining the content of education in the process of preparing job trainers and the instruments needed for the professional organization of the work environment for the mentees of the trainer were presented. Attention has been paid to the principle of departing from direct social transfers for the benefit of social and professional activation of the people at risk of social exclusion due to disability, adopted in the modern social policy, for example in supported employment. Also, there was emphasized the importance of education for shaping attitudes conducive to social inclusion of marginalized people. Keywords: education, social cohesion policy, supported employment, job coach, social inclusion   Edukacyjne aspekty zatrudnienia wspomaganego jako egzemplifikacja działań na rzecz polityki spójności społecznej na podstawie polskich doświadczeń Przedmiotem artykułu są rozważania dotyczące zaangażowania systemu edukacji na rzecz wdrażania polityki spójności społecznej na podstawie polskich doświadczeń. Przykładem takiego zaangażowania jest aktywność w procesie wdrażania projektu zatrudnienia wspomaganego, którego ważnym elementem jest przygotowanie trenerów pracy do wykonywania zadań zawodowych. Na tle przeprowadzonych badań zaprezentowano sposoby określania treści kształcenia w procesie przygotowania trenerów pracy oraz instrumentarium potrzebne do profesjonalnej organizacji środowiska pracy dla podopiecznych trenera. Zwrócono uwagę na przyjętą w nowocześnie prowadzonej polityce społecznej zasadę odchodzenia od bezpośrednich transferów socjalnych na rzecz aktywizacji społecznej i zawodowej osób zagrożonych wykluczeniem społecznym ze względu na niepełnosprawność, której przykładem jest zatrudnienie wspomagane. Podkreślono znaczenie edukacji na rzecz kształtowania postaw sprzyjających inkluzji społecznej osób marginalizowanych.